Pengaruh Arus Kas Bebas, Ukuran KAP, Spesialisasi Industri KAP, Audit Tenur dan Independensi Auditor terhadap Manajemen Laba - Fransiska Dian Fransiska Dian; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2013)
This study aimed to analysze the effect of free cash flow, size of auditor firm,auditor firm industry specialization, audit tenure and auditor independence on earnings management. Auditor independence in this study is measured by client importance. Earnings management in this study is measured by total discretionary accruals of the company. The population of this study is the manufacture companies listed in Indonesia Stock Exchange year period 2009-2011. Sampling method that’s used in this study is purposive sampling. The total number of sample in this study are 138 research samples. However, there are found 30 sample as outlier should be excluded from sample of observation. So, the final amounts of the sample are 108 research samples. The analysis technique in this study uses a multiple regression analysis with help from a program named SPSS. The analysis technique in this study uses a multiple regression analysis with help from a program named SPSS. The analysis technique in this study uses a multiple regression analysis with help from a program named SPSS. The result of this study indicate that the free cash flow negative effect on earnings management. Meanwhile, size of auditor firm, auditor firm industry specialization, client importance and audit tenure has no significantly impact on earning management.